Factors Affecting Interest Return Working For Star Hotel Workers In The Seminyak Area - Ni Putu Putri Widyaningsih; I Gusti Ngurah Widyatmaja; Ni Putu Ratna Sari (Cita Konsultindo Research Center, 2023)
Bali is one of the tourism destinations that has been hit hard by the Covid-19 pandemic. The crisis facing the tourism sector has had a major impact on workers, including hotel workers. Many hotels lost money and closed so they were forced to lay off their workers, including five-star hotels in the Seminyak area. Problems arise when tourism conditions in Bali begin to recover and the tourism industry has difficulty finding experienced workers. For this reason, this study aims to reveal the factors that influence star hotel workers to return to work in the tourism industry in post-pandemic conditions. This study uses a mixed approach (mix methods) which combines quantitative and qualitative approaches. The sampling technique used is technique purposive sampling and data collected through questionnaires, interviews, documentation studies and observation. Interviews were conducted on 7 informants and questionnaires distributed to 135 respondents. Quantitative data analysis techniques were carried out using confirmatory factor analysis techniques (Confirmatory Factor Analysis /CFA) which is processed in a statistical program software. The results of the study found that most of the respondents returned to work in the tourism industry and there were 6 factors that influenced workers' interest in returning to the tourism industry, namely non-physical environmental factors, as the most dominant factor, followed by the nature of work, workers' rights factors, social status factors, skill and character factors, and lastly, the religious value factor